2019
DOI: 10.1128/aac.02588-18
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1, Randomized, Single-Ascending-Dose Study To Investigate the Safety, Tolerability, and Pharmacokinetics of DSTA4637S, an Anti- Staphylococcus aureus Thiomab Antibody-Antibiotic Conjugate, in Healthy Volunteers

Abstract: Staphylococcus aureus causes serious bacterial infections with high morbidity and mortality, necessitating the discovery of new antibiotics. DSTA4637S is a novel antibody-antibiotic conjugate designed to target intracellular S. aureus that is not adequately eliminated by current standard-of-care antibiotics. DSTA4637S is composed of an anti-S. aureus Thiomab human immunoglobulin G1 (IgG1) monoclonal antibody linked to a novel rifamycin-class antibiotic (4-dimethylaminopiperidino-hydroxybenzoxazino rifamycin [d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…The results demonstrated that the investigated DSTA4637A construct had almost no effect on noninfected mice and displayed a good PK/PD profile. Recently, this Ab–antibiotic conjugate was evaluated in phase 1 clinical trials in healthy volunteers, and the outcome was very promising, as no serious or severe adverse effects occurred . Moreover, no immune responses against DSTA4637S were observed, which confirmed the general hypothesis that such constructs should be safe for patients, as human cells do not express S. aureus antigens.…”
Section: Antibody–antibiotic Conjugatesmentioning
confidence: 82%
“…The results demonstrated that the investigated DSTA4637A construct had almost no effect on noninfected mice and displayed a good PK/PD profile. Recently, this Ab–antibiotic conjugate was evaluated in phase 1 clinical trials in healthy volunteers, and the outcome was very promising, as no serious or severe adverse effects occurred . Moreover, no immune responses against DSTA4637S were observed, which confirmed the general hypothesis that such constructs should be safe for patients, as human cells do not express S. aureus antigens.…”
Section: Antibody–antibiotic Conjugatesmentioning
confidence: 82%
“…In a murine model of hematogenous MRSA infection, use of the AAC reduced S. aureus bacteremia relative to systemic vancomycin alone in both wild type and severe combined immune deficiency spontaneous mutation mice 23 . A similar approach showed no toxicity in human Phase I clinical trials 127 …”
Section: New Advancements In the Treatment Of Musculoskeletal Infectionmentioning
confidence: 98%
“…Step 4, unconjugated dmDNA31 kills the intracellular bacteria. Reproduced with permission from: Peck et al 127 VS, valine‐citrulline [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: New Advancements In the Treatment Of Musculoskeletal Infectionmentioning
confidence: 99%
“…Of the 37 programs in the CARB-X portfolio for antibacterial treatment, over 48% are alternatives to traditional small molecule antibacterial agents [28]. Many products in various stages of development, from hit-to-lead to preclinical and clinical, that utilize these novel approaches are described in Table 2 [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. [25,27] For example, monoclonal antibodies have revolutionized cancer chemotherapy [39,40] and have the potential to do the same for the treatment and prevention of infectious diseases [25][26][27].…”
Section: Phage Therapies Virulence Inhibitors Bacterial Growth Ratementioning
confidence: 99%